Hydration and Barrier Potential of Cosmetic Matrices with Bee Products - Pavlačková, Jana; Egner, Pavlína; Slavík, Roman; Mokrejš, Pavel; Gál, Robert (Molecules (Basel, Switzerland), 2020)
Honey, honey extracts, and bee products belong to traditionally used bioactive molecules in many areas. The aim of the study was primarily to evaluate the effect of cosmetic matrices containing honey and bee products on the skin. The study is complemented by a questionnaire survey on the knowledge and awareness of the effects and potential uses of bee products. The effect of bee molecules at various concentrations was observed by applying 12 formulations to the skin of the volar side of the forearm by non-invasive bioengineering methods on a set of 24 volunteers for 48 h. Very good moisturizing properties have been found in matrices with the glycerin extract of honey. Matrices containing forest honey had better moisturizing effects than those containing flower honey. Barrier properties were enhanced by gradual absorption, especially in formulations with both glycerin and aqueous honey extract. The observed organoleptic properties of the matrices assessed by sensory analysis through 12 evaluators did not show statistically significant differences except for color and spreadability. There are differences in the ability to hydrate the skin, reduce the loss of epidermal water, and affect the pH of the skin surface, including the organoleptic properties between honey and bee product matrices according to their type and concentration.
Keywords: Emulsions; bee products; emulsion; koncentrace vodíkových iontů; průzkumy a dotazníky; transepidermal water loss; bioactive molecules; med; kosmetické přípravky; zvířata; Cosmetics; functional matrices; Hydrogen-Ion Concentration; Surveys and Questionnaires; hydration; Honey; honey; včely; emulze; Bees; organoleptic properties; cosmetics; Animals